DETERMINANT ANALYSIS OF FINANCIAL RATIO ON STOCK RETURNS IN CONSTRUCTION COMPANIES REGISTERED AT INDONESIA STOCK EXCHANGE 2015-2019 - Muhammad Reza Alfianto Siregar; Pardomuan Sihombing (Dinasti Publisher, 2020)
The growth of the construction sector in Indonesia has indirectly contributed to the growth in the performance of construction companies. This construction performance growth has an impact on stock price movements, apart from the influence of demand and supply of shares. The condition of fluctuating stock price movements requires investors to analyze financial statements before making investment decisions. To find out how the stock price performance can be done by measuring stock returns. In connection with these conditions, the purpose of this study is to analyze the effect of ROE, DER, CR, PBV and TATO on stock returns in construction companies listed on the IDX in 2015 - 2019. This research is included in the category of comparative causal research. The number of samples used in this study were 13 sample companies, with the sampling technique using purposive sampling. The type of data in this study is secondary data taken by the documentation method at Yahoo Finance. The data analysis method uses panel data regression analysis assisted by the Eviews 9.0 software. The results of the study partially show that ROE; DER, CR, PBV, and TATO have a positive and significant effect on stock returns. In addition, ROE, DER, CR, PBV, and TATO simultaneously have a significant effect on stock returns.